A Strangulated Congenital Diaphragmatic Bochdalek Hernia Diagnosed in an Adult. (20th July 2022) - Warsinggih, Warsinggih; Uwuratuw, Julianus Aboyaman; Arsyad, Arham; Faruk, Muhammad
Abstract : Although Bochdalek hernias are uncommon in adults and difficult to diagnose, such congenital diaphragmatic hernias (CDHs) are some of the most serious malformations among newborns. In particular, CDHs are accompanied by high mortality and marked disability later in life due to concomitant morbidity (i.e., caused by pulmonary lung hypoplasia and persisting pulmonary hypertension of neonates) and require long-lasting neonatal treatment in an intensive care unit. Late-diagnosed CDHs are extremely rare and always show small defects that justify a better prognosis than CDHs with large defects. In most cases, such CDHs go undiagnosed due to their mild, delayed symptoms. In the case described here, an 18-year-old Asian male presented with abdominal pain and a bowel contour in the epigastric region and left upper quadrant. A chest X-ray and thoracoabdominal computerized tomography scan confirmed the diagnosis of bowel obstruction due to a left diaphragmatic hernia. Moreover, a defect was revealed in the posterolateral left diaphragm, and the transverse colon, spleen, and half of the stomach had herniated through it. A segmentectomy was performed on the transverse colon, followed by an end-to-end anastomosis, a diaphragmatic plasty, and the placement of an intrapleural catheter. In conclusion, diagnosing a diaphragmatic hernia before surgery can be difficult due to its rarity and wide range of symptoms. Although prenatal diagnosis using ultrasonography is possible in up to 80% of fetuses, that method may not be available in all regions in Indonesia or in all countries, where doctors thus continue to face a diagnostic challenge when dealing with CDHs.